Research progress of SMR data in China and Japan. Issue 6 (25th January 2021) - Cai, Wenbin
Abstract : Purpose: This paper aims to make a comprehensive evaluation of the progress and achievements made by China and Japan in literature collection, publication and academic research of South Manchuria Railways Co (SMR) after the Second World War and points out the existing and urgent problems. Design/methodology/approach: This paper adopts the methods of literature research, questionnaire survey, comparative analysis and expert consultation. Findings: After the Second World War, both China and Japan made great achievements in the collection, publication and research of SMR data, as well as in the academic research of SMR. However, as a new research field, there are still some problems in deepening the excavation and utilization of SMR data, expanding the research fields, improving the research methods, etc. Originality/value: SMR itself was the product of a war of aggression. Although it died with the defeat of the war of aggression, remaining SMR data also has very precious value, it records the history of Japanese aggression against China, is the biggest database for the study of the problems in China and northeast Aisa at that time. In addition to Japan and China, the USA and the Soviet Union also kept part of the SMR data, so that to involve them in the research of SMR is also the purpose of this paper.